Sur le domaine de convergence de série de Dirichle - Miškelevičius, A. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. Мишкелявичус. Об области сходимости ряда ДирихлеA. Miškelevičius. Dirichle eilutės konvergencijos sritis